Porous Natural Diamond with Embedded Metal (Pt0.50–Co0.50) - Evgeny Filatov; Aleksei Chepurov; Valeri Sonin; Andrey Zadesenets; Sergey Gromilov; Egor Zhimulev (Chemistry, 2023)
Natural diamond crystals with a highly porous surface were used as substrates for synthesizing single-phase bimetallic Pt–Co nanoparticles at temperatures of 500 °C and 800 °C. The metal nanoparticles inside the pores were determined to take the form of single-phase Pt0.50Co0.50 solid solutions with different degrees of superstructure ordering. A detailed characterization of both nanoalloys revealed a tetragonal symmetry with a space group, P4/mmm. For the sample obtained at 500 °C, the lattice parameters were a = 2.673(2), c = 3.735(3) Å, and c/a = 1.397(1); for the samples obtained at 800 °C, the parameters were—a = 2.688(2), c = 3.697(3) Å, and c/a = 1.375(1). Within the experimental parameters, no significant chemical interaction of the diamond with the Pt–Co particles was identified. The results demonstrate a strong anchoring effect of the metallic material within the etching pores. The successful synthesis of bimetallic Pt–Co particles embedded inside the caverns can facilitate a study of their magnetic properties. The presence of Pt–Co in specific diamond compositions can also be used for marking diamond crystals as a means for their subtle identification, as well as confirming the possibility of capturing significant amounts of metal along with diamonds during their dissolution in the deep Earth.